Pengaruh Pemberian Penyuluhan Dengan Permainan Ular Tangga Terhadap Pengetahuan Dan Sikap Mengkonsumsi Jajanan Sehat Siswa- Siswi Kelas V Di SD Negeri 1 Sukarame Kota Bandar Lampung Tahun 2019 - pira prahmawati; Achmad Djamil (JIKMI (Jurnal Ilmu Kesehatan Masyarakat Indonesia), 2020)
AbsractBased on BPOM survey results, it shows that 99% of school children buy snacks at school. In addition, BPOM also still found foods containing textile dyes in traditional markets by generating data that exhibits  70% of production facilities, and 55% of drug and food distribution facilities in the city of Bandar Lampung didn’t  meet the requirements (BPOM, 2018).Thus, the purpose of this study was determining whether or not the effect of providing counseling with snakes and ladders game to  the knowledge and attitudes of consuming healthy snacks in the case of fifth grade students at SD Negeri 1 Sukarame, Bandar Lampung City. The type of this research is a pre-experimental study. The population of the study is 153 students with a sample of 61 respondents using the stratified random sampling technique to specify the number of students taken per class, then they would be conducted pre-test and post-test. Data were analyzed using the T test. The results of this research are an increase in knowledge and attitudes of respondents after the provision of counseling with snakes and ladders game. Prior to provide counseling using snakes and ladders game,  the average value of respondents knowledge was 51.72 to 67.97, and the average value of attitudes was 52.56 to 72.787. The results based on the T test obtained knowledge p-value 0,000 (<0,005), and attitude p-value 0,000 (<0,005), which means that there is an effect of giving counseling by playing snakes and ladders game to the knowledge and attitudes. Ultimately, this research also contains suggestions for voluntary SD Negeri 1 Bandar Lampung, especially to the teachers as The School Health Unit Supervisory Team (SHUPT/TPUKS) at school to give a basic knowledge about nutrition routinely, and fun learning media according to the age of school children.Keywords: healthy snacks, knowledge and attitudesof  healthy snacks